Present value of firm in case of correlated defaults - Mantas Valužis (Lietuvos Matematikos Rinkinys)
In this article, the valuation of firm’s present value in case of correlated defaults is studied. We showed that the valuation of portfolio credit risk can be interpreted as a valuation of the multiple contingent option. In this article, some results for valuation of multiple contingent options are generalized in case of stochastic barriers and the financial interpretation is given. Also, the modelling of other financial risks, notably, the market risk (the change of debt value) and the operational risk (the adequacy of selected credibility criteria) are included in these theorems. Using the principle of conservatism in credit risk assessment, the debtor credibility, the debt value and the firm value are assumed to follow geometric Wiener process.